Coating and lamination of Nafion117 with partially sulfonated PVdF for low methanol crossover in DMFC applications. (10th August 2015) - Kumar, Piyush; Kundu, Patit Paban
Highlights: Successful sulfonation of PVdF in the presence of chlorosulfonic acid. Utilization of S-PVdF as coated and/or laminate material on Nafion. Lower methanol crossover compare to pristine Nafion-117. 6-7 times high selectivity ratio than the pristine Nafion-117. Maximum cell performance was 47 mW cm −2 recorded for Nafion-SPL. Abstract: Sulfonation of PVdF was carried out in the presence of chlorosulfonic acid at 60 °C. The presence of characteristic peaks of sulfonic acid in the FT-IR spectra confirmed the successful sulfonation of PVdF. X-ray diffraction was conducted to analyze the effect of sulfonation on the crystallinity of PVdF. On sulfonation for a period of 2 h, the maximum DS value achieved was 33%. This sulfonated PVdF resin was utilized as a laminate and/or coating material for the modification of Nafion-117. The laminated and coated Nafion-117 as polymer electrolyte membranes in direct methanol fuel cell (DMFC) exhibited significantly lower methanol crossover by magnitude of two orders, leading to their respective higher membrane selectivities and OCV (open circuit voltage) over prisine Nafion-117 membrane. By operating the DMFC with highly concentrated methanol (5 M), the cell efficiency (maximum power density) for the laminated and coated Nafion 117 membranes was found to be superior over that of pristine Nafion-117.